Adsorption of Sulphur Dioxide on Zirconium Vanadophosphate for Flue Gas Clean Up - Gupta, H.O. (Asian Journal of Chemistry, 2010)
The scrubbing of sulphur dioxide from the flue gas by adsorption reaction between the gas and synthetic mineral, zirconium vanadophosphate (Zr.V.P.), was investigated by passing simulated flue gas through a fixed bed reactor of fully swelled exchanger material. The influence of carbon dioxide and water vapour present in the flue gas was studied in the temperature range of 40º to 100ºC. The adsorption of sulphur dioxide on Zr.V.P. is reversible and can be desorbed by eluting with 0.1 % hydrogen peroxide, collecting the sulphuric acid in the effluent. The scrubber has been designed to remove the SO2 gas from flue gas; the capacity was measured 70 mg SO2 per gram of exchanger material. The infrared studies confirm the adsorption of SO2 in the frequency range 1500–1600 cm–1 on the O–H bond of which the bending frequency appeared as 1630 cm–1 in the molecular structure of pure Zr.V.P.